Students’ Engagement of Social Networking Sites: An Evaluation of Perception, Gratification, Sociability, Academic and Generalized Usage Patterns - Asad Khan (Pakistan Journal of Information Management & Libraries, 2018)
Students' engagement of Social Networking Sites (SNS) has substantially influenced their social, personal, and academic lives. However whether students in Pakistani universities are aware of its roles and its respective influence has rarely been investigated. The aim of this study is to evaluate students' behavioral attitude (perceptions, gratification, awareness, usage patterns etc.) towards SNS. Using self-administered survey questionnaires, data were collected from a sample of postgraduate students at the University of Peshawar, Pakistan. The findings revealed a significant level of awareness of the role of SNS, of which YouTube, Facebook, and Flicker are widely used sites by the study participants. However, generalized use of SNS specifically, Wiki, RSS, Twitter, and MySpace is not considered academic or for research purposes, but for sheer gratification, and sociability. Further, laptops and smart phones were found to be the primary tools of access to SNS at university and/or homes. Additionally, entertainment and friendship were specified as the foremost prompts for using SNS. A primary obstacle indicated by participants is power failure. This study has manifold implications such as: a) social implications- parents and teachers should educate students about the inventive, academic, and safe use of SNS. This will impede the ills of SNS that have resulted in the reduction of learning and research capabilities; b) practical implications- authorities should make more precise policies for the use of SNS in the universities. To this end class orientations are suggested to inform students about the academic use of SNS and; c) theoretical implications- as students' intention of using SNS are gratification, sociability etc., thus the theory of Uses and Gratification is supported.